Substituted judgment for the never-capacitated: Crossing Storar's bridge too far - Appel, Jacob M. (Bioethics, 2022)
Since several landmark legal decisions in the 1970s and 1980s, substituted judgment has become widely accepted as an approach to decision-making for incapacitated patients that incorporates their autonomy and interests. Two notable exceptions have been cases involving minors and those involving cognitively or psychiatrically impaired individuals who never previously possessed the ability to contemplate the medical decisions involved in their care. While a best interest standard may have universal merit in pediatric cases, this paper argues that substituted judgement has been rejected too broadly for “never-capacitated” patients. It then lays out a three-condition test for using substituted judgment in these cases. For a subset of “never-capacitated” patients who belong to distinctive religious or cultural communities with clear medical values and have an appropriate surrogate, these values may prove helpful in vindicating the interests of the never-capacitated and should not be blanketly dismissed.